TINJAUAN YURIDIS KLAUSULA BAKU DALAM PERJANJIAN KEMITRAAN CV. BERKAH MAJU REJEKI DENGAN PETERNAK AYAM BROILER ( Studi pada Kia Jaya Bersama Farm di Deli Serdang) - Adist Ayudistira; Marsella Marsella; Ridho Mubarrak (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
Although the government has issued various policies that can help plasma growers, the partnership model that appears in reality is a standard agreement or standard, and plasma growers have no freedom to negotiate the content of the agreement. The research methods is a normative law with analytical descriptive. The research methods are Library Research, namely research conducted based on reading sources, namely laws, books, scientific research, mass media, legal journals related to the material discussed in this mini-thesis. In this research there are primary data and secondary data and Field research, that is, direct research in the field. In this case, the researchers interviewed CV. BerkahMajuRejeki and Kia Jaya Bersama farms directly. As is obtained from further research begins qualitatively.  The research results obtained are The standard clauses in the cooperation agreement between Kia Jaya Bersama and CV. BerkahMaju Rejeki loss caused that must be borne by Kia Jaya Bersama Farm itself, and the company did not provide a solution. Therefore, the author believes that the terms of this partnership agreement do not provide the same benefits and advantages for both parties.